KONTRIBUSI SEKTOR PERTANIAN DALAM PENYEDIAAN LAPANGAN KERJA DAN PERBANDINGANNYA DENGAN SEKTOR-SEKTOR LAIN - SYAM, AMIRUDDIN; NOEKMAN, KHAIRINA M. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 1 Februari 2003, 2012)
The objective of the study is to assess the performance of labor force by sector. It followed by the comparison among sectors. The study found that: (1) The labor force absorption role between 1985-1989, dominated by agricultural sector which was 56.66% of all other sector absorption rate were only 5 – 13%, (2) In the shorterm, the labor force absorption rate of services and agricultural sectors are not as. Persistent as industrial and trade sectors. However, in the long run, the absorption rate of agricultural sectors are persistently compared to industry and trade, (3) Agricultural sectors are relatively more stable in the absorption of labor force compared to other sectors.
Keywords: Labor Force Absorption, Agricultural Sector, Service Sector, Industrial and Trade sectors